The Association between APOE Genotype and Memory Dysfunction in Subjects with Mild Cognitive Impairment Is Related to Age and Alzheimer Pathology - Ramakers, I.H.G.B.; Visser, P.J.; Aalten, P.; Bekers, O.; Sleegers, K.; van Broeckhoven, C.L.; Jolles, J.; Verhey, F.R.J. (Dementia and geriatric cognitive disorders, 2008)
Background: Memory problems are a main feature of mild cognitive impairment (MCI) and may be related to the apolipoprotein E (APOE) Ε4 allele. We investigated whether the effect of the APOE genotype on memory in subjects with MCI was dependent on age and underlying Alzheimer disease (AD) pathology. Methods: Subjects with MCI (n = 180) were selected from a memory clinic setting. Subjects with at least one APOE Ε4 allele (n = 83) were compared to non-carriers on several memory measures. Subjects were reassessed 5–10 years later in order to identify those who developed AD. Results: In the middle-aged subgroup, the APOE Ε4 allele was most strongly related to decreased subjective organization and in the old subgroup to a decreased delayed recall. After excluding subjects with incipient AD (n = 33), results remained similar in the middle-aged subgroup, but in the old subgroup the APOE genotype was no longer associated with memory dysfunction. Conclusion: The presence of the APOE Ε4 allele is associated with impaired memory functioning in both middle-aged and old subjects with MCI, although the memory function affected varies with age. Its effect on memory function may be dependent on underlying AD pathology in elderly subjects, but not in middle-aged subjects.